Tháng Tư 15, 2024

(2đ) Rút gọn rồi tính giá trị các phân thức sau: a) \(A = \frac{{(2{x^2} + 2x){{(x – 2)}^2}}}{{({x^3} – 4x)(x + 1)}}\) với \(x = \frac{1}{2}\) b) \(B = \frac{{{x^3} – {x^2}y + x{y^2}}}{{{x^3} + {y^3}}}\) với \(x = – 5;\,\,y = 10.\)

(2đ) Rút gọn rồi tính giá trị các phân thức sau:

a) \(A = \frac{{(2{x^2} + 2x){{(x – 2)}^2}}}{{({x^3} – 4x)(x + 1)}}\) với \(x = \frac{1}{2}\)

b) \(B = \frac{{{x^3} – {x^2}y + x{y^2}}}{{{x^3} + {y^3}}}\) với \(x = – 5;\,\,y = 10.\)

Lời giải chi tiết:

a) \(A = \frac{{(2{x^2} + 2x){{(x – 2)}^2}}}{{({x^3} – 4x)(x + 1)}}\) với \(x = \frac{1}{2}.\)

Ta có: \(A = \frac{{(2{x^2} + 2x){{(x – 2)}^2}}}{{({x^3} – 4x)(x + 1)}} = \frac{{2x(x + 1){{(x – 2)}^2}}}{{x({x^2} – 4)(x + 1)}} = \frac{{2x(x + 1){{(x – 2)}^2}}}{{x(x – 2)(x + 2)(x + 1)}} = \frac{{2(x – 2)}}{{x + 2}}.\)

Thay \(x = \frac{1}{2}\) vào biểu thức \(A\), ta được:

\(A = \frac{{2\left( {\frac{1}{2} – 2} \right)}}{{\frac{1}{2} + 2}} = \frac{{2.\left( {\frac{{ – 3}}{2}} \right)}}{{\frac{5}{2}}} = \frac{{ – 3}}{{\frac{5}{2}}} = \frac{{ – 6}}{5}.\)

b) \(B = \frac{{{x^3} – {x^2}y + x{y^2}}}{{{x^3} + {y^3}}}\) với \(x = – 5;\,\,y = 10.\)

Ta có: \(B = \frac{{{x^3} – {x^2}y + x{y^2}}}{{{x^3} + {y^3}}} = \frac{{x({x^2} – xy + {y^2})}}{{(x + y)({x^2} – xy + {y^2})}} = \frac{x}{{x + y}}.\)

Thay \(x = – 5;\,\,y = 10.\) vào biểu thức \(B\), ta được:

\(B = \frac{{ – 5}}{{ – 5 + 10}} = \frac{{ – 5}}{5} = – 1.\)